The Surrealistic Invention in the Poetry of Henrikas Radauskas - Naujokaitienė, Elina (Respectus Philologicus, 2004)
Henrikas Radauskas, a poet of the Lithuanian exile, has created hermetic poetry. He utilises a number of poetical associations to give reference to the world of plastic art. His artistic fancy takes much from picturesque imagination of Lithuanian folklore as well as from surrealist paintings. The surrealistic aesthetic of Radauskas has its roots in the theories of French surrealist poets. In the American culture he finds new Lithuanian and European sources. Lithuanian folk tales are amalgamated with surrealist literary sources. An analogy between Radauskas and André Breton has been made. In this article the method of comparative literature has been used. Fragments of Lithuanian translations of pieces of poetry of Breton have been presented in order to show their resemblance. The article shows how the concept of the normative role in culture is linked with the art of elite. Remarks are made how the modernist trends find their way in the complex popular post-modernist culture. The poems „An Arrow in the Sky" by Radauskas and „The Ascending Sign" by Breton have been analysed.